Autoestima y Habilidades Sociales en Escolares. Centro de Desarrollo de la Niñez Amiguitos de Cristo, Riobamba, 2018 - Millán Ramos, Keren Elizabeth (2019)
The present reseach work addresses the Self-esteem and Social Skills in the children of the “Amiguitos de Cristo” Child Development Center, Riobamba, during the period 2018. The population consisted of 45 boys and girls who were part of the development center of childhood and in that way to be able to analyze the Self-Esteem and Social Skills. In the research project were: “Rosemberg Self-Esteem Scale” and “Goldstein Social Skills Questionnaire” that identifies the presents levels. The main results are obtaining that: 53.3 % presented an average level of self-esteem, 46.7 % showed a low level of self-esteem, while effects whit high self-esteem could not observe in this study. It identified 62.2 % of children whit an average level of social skills, 37.8 % who have a low level of social skills, and the children presented values of Social Self-Esteem and Skills at a medium level. They usually tend to develop in a standard social environment and global environment; otherwise, the case is notorious their phase shifts. Finally, this project, it is recommended to follow up on the prevention plan that is applied to know the results and if it is necessary to improve.